2010
DOI: 10.1128/jvi.02317-09
|View full text |Cite
|
Sign up to set email alerts
|

The N Terminus of Adenovirus Type 12 E1A Inhibits Major Histocompatibility Complex Class I Expression by Preventing Phosphorylation of NF-κB p65 Ser 276 through Direct Binding

Abstract: The immune-escape strategy employed by human oncogenic adenovirus type 12 (Ad12) involves downregulation of major histocompatibility complex class I (MHC-I) transcription by disabling the transactivator NF-B (p50/p65). This is accomplished by the Ad12 E1A protein (E1A-12), which prevents NF-B from becoming phosphorylated by the protein kinase A catalytic subunit (PKAc). In this study, we examined the interactions between E1A-12 and NF-B. Our data show that an E1A-12 mutant retaining the N-terminal 66 amino aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 37 publications
(58 reference statements)
0
9
0
Order By: Relevance
“…The human adenovirus type 12(Ad12) E1A protein (E1A-12) inhibits phosphorylation of NF-κB p65 at Ser 276 and causes the loss of DNA binding and transactivation to activate major histocompatibility complex class I expression [10]. Further study found that the last 66 amino acids of the N-terminus of adenovirus type 12 E1A were as effective as the wild-type E1A protein in preventing phosphorylation of NF-κB p65 at Ser 276 and inhibiting major histocompatibility complex class I expression [11]. Our previous report indicated that the ORFV002 gene inhibits the NF-κB signaling pathway by decreasing TNF-α.…”
Section: Introductionmentioning
confidence: 99%
“…The human adenovirus type 12(Ad12) E1A protein (E1A-12) inhibits phosphorylation of NF-κB p65 at Ser 276 and causes the loss of DNA binding and transactivation to activate major histocompatibility complex class I expression [10]. Further study found that the last 66 amino acids of the N-terminus of adenovirus type 12 E1A were as effective as the wild-type E1A protein in preventing phosphorylation of NF-κB p65 at Ser 276 and inhibiting major histocompatibility complex class I expression [11]. Our previous report indicated that the ORFV002 gene inhibits the NF-κB signaling pathway by decreasing TNF-α.…”
Section: Introductionmentioning
confidence: 99%
“…For example, E1A12 but not E1A5 can enhance the transcriptional repression function of the orphan NR COUP‐TFII (also known as NR2F2) . E1A12, but not E1A5, has been reported to inhibit the phosphorylation of the p65 subunit of NF‐κB by the protein kinase A catalytic subunit (PKAc), resulting in the suppression of NF‐κB‐mediated transactivation . We report here that E1A12 binds to the AR and suppresses the transactivation function of AR.…”
Section: Introductionmentioning
confidence: 83%
“…Consequently, E1As of different serotypes may exert considerable functional differences. Indeed, distinct functions have been observed for Ad12 E1A (herein referred to as E1A12) . For example, E1A12 but not E1A5 can enhance the transcriptional repression function of the orphan NR COUP‐TFII (also known as NR2F2) .…”
Section: Introductionmentioning
confidence: 99%
“…Poxviruses and herpes viruses have evolved multiple strategies to disrupt presentation of viral antigens by MHC molecules in order to evade control by T lymphocytes [12]. The adenovirus inhibits MHC-I molecules to evade immune detection [13]. Viruses have also developed mechanisms to bolster the host cell to withstand the viral replication process such as an inhibition of apoptosis [14], an induction of cellular growth or differentiation [15], a recruitment of tissue repair processes such as fibrosis [16], tissue growth [17], and angiogenesis [18].…”
Section: Introductionmentioning
confidence: 99%